2014
DOI: 10.1021/jp5048634
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution and Frustrated Antiferromagnetic Coupling Effects on the Magnetic Behavior of Ultrafine Akaganéite (β-FeOOH) Nanoparticles

Abstract: The magnetic properties of low dimensional materials of several iron oxyhydroxyde phases, such as akaganéite (β-FeOOH) or lepidocrocite (γ-FeO(OH)), remain poorly explored; probably due to their specific preparation as single crystalline phase requires special conditions owing to their structural instability. In the present work, ultra-fine akaganéite nanoparticles were prepared by the hydrolysis of FeCl 3 solutions at room temperature induced by the presence of NaOH. The resulting product was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 56 publications
4
37
0
Order By: Relevance
“…Luna et al reported magnetic properties of akaganeite nanocrystals with mean diameter of (3.3 ± 0.5) nm and with a small amount of rodlike akaganeite particles with (23 ± 5) nm in length and (5 ± 1) nm in diameter. 20 These studies revealed complex magnetic relaxation processes, high values of coercivity and an exchange bias effect, both at low temperatures. The conclusion was that these results arise from the frustration of the antiferromagnetic order owing to surface effects and an insufficient filling of akaganeite channels with Cl -anions.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Luna et al reported magnetic properties of akaganeite nanocrystals with mean diameter of (3.3 ± 0.5) nm and with a small amount of rodlike akaganeite particles with (23 ± 5) nm in length and (5 ± 1) nm in diameter. 20 These studies revealed complex magnetic relaxation processes, high values of coercivity and an exchange bias effect, both at low temperatures. The conclusion was that these results arise from the frustration of the antiferromagnetic order owing to surface effects and an insufficient filling of akaganeite channels with Cl -anions.…”
Section: Introductionmentioning
confidence: 95%
“…a spin imbalance due to a lack of particles' structural perfection. [19][20][21] Among antiferromagnetic iron oxides and hydroxides, akaganeite is less well known, possibly due to the inherent difficulties in preparation of a single crystalline phase: such a preparation requires special conditions owing to the akaganeite's structural instability. 20 Akaganeite is interesting due to its structural, magnetic and catalytic properties, as well as for practical applications such as for the removal of pollutants, sorption, ion-exchange, lithium-air batteries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, shape-controlled synthesis of one-dimensional -FeOOH nanomaterials, in particular rods, fibers and wires, has attracted the increasing attention in recent years [1,3,11]. -FeOOH nanoparticles were traditionally prepared through hydrolysis of FeCl 3 in acidic or basic media.…”
Section: Introductionmentioning
confidence: 99%